2014
DOI: 10.1080/13611267.2014.927096
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Mentor Efficacy and Perceptions Following Participation in a Youth Mentoring Program

Abstract: Gresham, ORAlthough mentoring programs are increasing in popularity as a preventative intervention strategy for youth, little is known about the experience from the mentor's perspective. In this study, we describe a longitudinal assessment of 41 mentors, including 13 men and 28 women (M age = 21.93 years, SD = 3.21) working with at-risk youth in a school-based mentoring program. Before starting the program, mentor perceptions, motives, and efficacy were assessed and again after three and six months of mentorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 51 publications
(153 reference statements)
0
18
0
Order By: Relevance
“…Through a series of interviews with mentors involved in a formal mentoring program, mentors reported developing a personal relationship with their mentee . Mentors also reported feeling gratification watching the mentee develop new skills . Acting as a mentor can involve functions such as leadership and role‐modelling, which have been seen to improve emotional well‐being for the mentor .…”
Section: Introductionmentioning
confidence: 99%
“…Through a series of interviews with mentors involved in a formal mentoring program, mentors reported developing a personal relationship with their mentee . Mentors also reported feeling gratification watching the mentee develop new skills . Acting as a mentor can involve functions such as leadership and role‐modelling, which have been seen to improve emotional well‐being for the mentor .…”
Section: Introductionmentioning
confidence: 99%
“…A mentor’s self-efficacy has been strongly associated with positive outcomes. Strapp et al (2014), in their longitudinal study of 41 mentors, found that mentors with higher self-efficacy tended to meet more frequently and regularly with their mentees and demonstrated higher degrees of persistence. Beyond their initial possession of significant levels of self-efficacy (Parra, DuBois, Neville, Pugh-Lilly, & Povinelli, 2002), mentor self-efficacy has been demonstrated to have improved according to their perceptions of having received quality training and ongoing, high-quality support (Lakind et al, 2014; Strapp et al, 2014).…”
Section: Informing Literaturementioning
confidence: 98%
“…Much of the extant research into SBM indicates that the most significant factor in determining the success or failure of mentoring to promote positive developmental outcomes has been the quality of the mentor. DuBois et al (2002, 2011) suggested that a mentor’s quality corresponds to their expression of a range of attributes which have been strongly correlated to significant outcomes across several studies (Allen & Eby, 2011; Grossman, Chan, Schwartz, & Rhodes, 2012; Kanchewa, Rhodes, Schwartz, & Olsho, 2014; Lakind, Eddy, & Zell, 2014; Strapp et al, 2014). These attributes are as follows: (a) capacity to commit to mentoring relationships, (b) personal characteristics, (c) self-efficacy, and (d) professional status.…”
Section: Informing Literaturementioning
confidence: 99%
“…Such mentor attributes and interpersonal skills have been considered key ingredients of highquality relationships and enables mentees to develop perceptions of emotional safety (Kanchewa et al, 2017). When mentors have prior experience in helping backgrounds, they may enter mentoring relationships with higher levels of selfefficacy, a variable that has been associated with successful mentor-mentee relationships (Dutton, Bullen, & Deane, 2018;Karcher, Nakkula, & Harris, 2005;Keller, 2005;Raposa, Rhodes, & Herrera, 2016;Strapp et al, 2014). For instance, mentors with high self-efficacy have been shown to provide more consistent support and to persevere during challenges with their mentees (Karcher et al, 2005;Parra, DuBois, Neville, Pugh-Lilly, & Povinelli, 2002;Strapp et al, 2014).…”
Section: Background Of Mentors Mentors Who Have Prior Experience Inmentioning
confidence: 99%
“…When mentors have prior experience in helping backgrounds, they may enter mentoring relationships with higher levels of selfefficacy, a variable that has been associated with successful mentor-mentee relationships (Dutton, Bullen, & Deane, 2018;Karcher, Nakkula, & Harris, 2005;Keller, 2005;Raposa, Rhodes, & Herrera, 2016;Strapp et al, 2014). For instance, mentors with high self-efficacy have been shown to provide more consistent support and to persevere during challenges with their mentees (Karcher et al, 2005;Parra, DuBois, Neville, Pugh-Lilly, & Povinelli, 2002;Strapp et al, 2014). Comparatively, mentors with low self-efficacy have been shown to give up more easily during challenges with mentees, due to feeling overwhelmed and unappreciated (Hamilton & Hamilton, 1992;Karcher et al, 2005;Strapp et al, 2014).…”
Section: Background Of Mentors Mentors Who Have Prior Experience Inmentioning
confidence: 99%